浅析新加坡华语广告里的语用含糊现象 = Pragmatic vagueness in Singapore Chinese advertising language - 邱凯铃 Khoo, Esther Kai Leng (2010)
广告语言是构成广告的重要部分之一。有时为了能吸引消费者的注意，广告商会采用某些语言策略来制造一些广告效果。广告里最常见的语言策略之一既是使用含糊的语言（语用含糊）。本文一共搜集了三十则有关健康与美容产品的新加坡华语广告，找出这些广告之中最常见的语用含糊现象。本文以Ruth Kempson的“含糊”概念为基础，把这些语用含糊现象归纳为三个类型。它们分别为“语义细节不明确类型”、“语义延伸类型”、和“多种语义解释类型”。然后，在个别类型之中进行分析，探讨这些语用含糊现象在广告之中所引起的效果。一般相信广告语境在消费者解读含有语用含糊现象的广告时，起着重要的功能。而消费者本身与消费者周遭的社会环境是构成广告语境的部分元素之一。因此，本文也将略谈消费者本身和社会环境在解读广告过程中所扮演的角色。Advertising language constitutes an important part in the advertisements. Sometimes, in order to attract the consumers’ attention on the advertisements, advertisers would adopt certain strategies in creating advertising language, so as to attain certain advertising effects. One of the most common strategies that advertisers adopt in advertising language is the usage of vague language (pragmatic vagueness). This thesis gathered a total of 30 Singapore mandarin advertisements, which are mainly related to healthcare and beauty products. Among these advertisements, several common pragmatic vagueness phenomena were identified. Based on Ruth Kempson’s concept on vagueness, the thesis classifies these commonly seen phenomena into 3 main types. The 3 types are namely “the use of words with indeterminate meanings”, “the use of words with extended meanings” and “the use of words with multiple meanings”. Following on, the thesis will also discuss the positive advertising effects of each type of pragmatic vagueness phenomena. It is believed that when the consumers were decoding the messages in the advertisements, which contain pragmatic vagueness phenomena, advertising context serves as an important function. Both the consumers and the social environment constitute part of the advertising context. Hence, the thesis will also discuss the roles of the consumers and social environment during the process when the consumers are decoding the message the advertisement is trying to deliver.